Modulation of Telomeres in Alternative Lengthening of Telomeres Type I Like Human Cells by the Expression of Werner Protein and Telomerase. (28th March 2012) - Siddiqa, Aisha; Cavazos, David; Chavez, Jeffery; Long, Linda; Marciniak, Robert A.
Abstract : The alternative lengthening of telomeres (ALT) is a recombination-based mechanism of telomere maintenance activated in 5–20% of human cancers. In Saccharomyces cerevisiae, survivors that arise after inactivation of telomerase can be classified as type I or type II ALT. In type I, telomeres have a tandem array structure, with each subunit consisting of a subtelomeric Y′ element and short telomere sequence. Telomeres in type II have only long telomere repeats and require Sgs1, the S. cerevisiae RecQ family helicase. We previously described the first human ALT cell line, AG11395, that has a telomere structure similar to type I ALT yeast cells. This cell line lacks the activity of the Werner syndrome protein, a human RecQ helicase. The telomeres in this cell line consist of tandem repeats containing SV40 DNA, including the origin of replication, and telomere sequence. We investigated the role of the SV40 origin of replication and the effects of Werner protein and telomerase on telomere structure and maintenance in AG11395 cells. We report that the expression of Werner protein facilitates the transition in human cells of ALT type I like telomeres to type II like telomeres in some aspects. These findings have implications for the diagnosis and treatment of cancer.